A new cost of ownership model for the acquisition of technology complying with environmental regulations. (1st August 2015) - Sohn, So Young; Jeon, Jeasu; Han, Eun Jin
Abstract: Firms in industries that pose environmental hazards are striving to acquire new technologies to meet tightened environmental regulations. Typically such firms have three main alternatives for obtaining technologies complying with the regulations: in-house development, purchasing a license, or merger and acquisition (M&A). In this paper, a new cost of ownership model that can assist selecting the best option to meet the regulation over the product lifetime is proposed. In order to forecast the demand for new products complying with environmental regulations, we apply Norton and Bass model. Our proposed evaluation model is applied to a case of heavy-duty diesel engine (HDDE) technology. According to our findings, purchasing a license is the most profitable alternative, while M&A and in-house development are sensitive to product lifetime and the expected lead-time for success, respectively. Our study is expected to support a firm's decision making process for selecting the best alternative for cleaner production. Highlights: A cost of ownership model is proposed to assist selecting the best option. We forecast the demand for new products complying with environmental regulations. We compare three options for technology acquisition and perform a sensitivity analysis. Our model is applied to a case of heavy-duty diesel engine (HDDE) technology.